2014
DOI: 10.1002/adhm.201300601
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Dendrimer–Doxorubicin Conjugate‐Based Nanoparticles as an Enzyme‐Responsive Drug Delivery System for Cancer Therapy

Abstract: Peptide dendrimers have shown promise as an attractive platform for drug delivery. In this study, mPEGylated peptide dendrimer-doxorubicin (dendrimer-DOX) conjugate-based nanoparticle is prepared and characterized as an enzyme-responsive drug delivery vehicle. The drug DOX is conjugated to the periphery of dendrimer via an enzyme-responsive tetra-peptide linker Gly-Phe-Leu-Gly (GFLG). The dendrimer-DOX conjugate can self-assemble into nanoparticle, which is confirmed by dynamic light scattering, scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 60 publications
(71 reference statements)
3
79
0
1
Order By: Relevance
“…Nevertheless, varying degrees of heart, and liver damages were observed from H&E stained organ slices in all the DOX involved groups. Obvious cardiotoxicity was induced by DOX plus CDDP treated groups due to the observed hyperemia, myocardial fiber breakage with acute inflammatory cell infiltration, critical pathological changes, and necrosis of the muscle fibers in cardiac tissue, which was in consistent with the previous report [43]. In contrast, the treatment of tumor bearing mice by DOX-encapsulated CL-Nanoparticles obviously reduced the blight of heart.…”
Section: Tumor Accumulation and In Vivo Antitumor Effect In Subcutanesupporting
confidence: 85%
“…Nevertheless, varying degrees of heart, and liver damages were observed from H&E stained organ slices in all the DOX involved groups. Obvious cardiotoxicity was induced by DOX plus CDDP treated groups due to the observed hyperemia, myocardial fiber breakage with acute inflammatory cell infiltration, critical pathological changes, and necrosis of the muscle fibers in cardiac tissue, which was in consistent with the previous report [43]. In contrast, the treatment of tumor bearing mice by DOX-encapsulated CL-Nanoparticles obviously reduced the blight of heart.…”
Section: Tumor Accumulation and In Vivo Antitumor Effect In Subcutanesupporting
confidence: 85%
“…As a consequence, it may be advantageous to use dendrimers as DOX carriers [41]. It has been shown that DOX can be either encapsulated within dendrimers via physical encapsulation/complexation [2,42] or conjugated onto the surface of dendrimers via a covalent linkage [43][44][45][46]. Each method has its own advantages and drawbacks.…”
Section: Introductionmentioning
confidence: 98%
“…Within the last decade, persistent efforts have been made in the development of stimuli-responsive drug delivery systems that can, when exposed to external stimuli, produce physicochemical changes that favor drug release at the target site. Depending on the target, typical biological stimuli have been exploited for triggered drug release including temperature [1], pH [2][3][4], magnetic field [5,6], redox potential [7][8][9], enzymes [10][11][12] or two parameters at the same time [13][14][15]. pH controlled release systems are particularly more interesting because we can find physiologically the pH gradients relevant for drug targeting.…”
Section: Introductionmentioning
confidence: 99%